2023
DOI: 10.1002/cpp.2913
|View full text |Cite
|
Sign up to set email alerts
|

In search of hidden threats: A scoping review on paranoid presentations in personality disorders

Erika Fanti,
Marco Di Sarno,
Rossella Di Pierro

Abstract: Recent diagnostic developments suggest that paranoia is a transdiagnostic characteristic common to several personality disorders rather than a personality disorder per se. Nonetheless, empirical literature fails to provide comprehensive and univocal findings on whether and how paranoid presentations relate to different personality disorders. In the present scoping review, we map the empirical literature on paranoid presentations in personality disorders, considering the entire spectrum of paranoid manifestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 152 publications
(312 reference statements)
0
3
0
Order By: Relevance
“…Paranoid and schizoid PDs are special cases because, despite their long history, there is a paucity of empirical research on those disorders, possibly stemming in part from the practical difficulty in recruiting such patients (Fanti et al, 2023; Triebwasser et al, 2013). Those limited evidence bases also led to their removal in the DSM‐5‐TR Alternative Model for Personality Disorders (American Psychiatric Association, 2022); it is suggested that they might be better construed as subtypes/cooccurrences of other PDs or be captured by the new trait‐specified PD (e.g., with traits such as Intimacy Avoidance, Suspiciousness, or Withdrawal; Skodol et al, 2011).…”
Section: Examples Where Pds and Psychotic Symptoms Meetmentioning
confidence: 99%
See 1 more Smart Citation
“…Paranoid and schizoid PDs are special cases because, despite their long history, there is a paucity of empirical research on those disorders, possibly stemming in part from the practical difficulty in recruiting such patients (Fanti et al, 2023; Triebwasser et al, 2013). Those limited evidence bases also led to their removal in the DSM‐5‐TR Alternative Model for Personality Disorders (American Psychiatric Association, 2022); it is suggested that they might be better construed as subtypes/cooccurrences of other PDs or be captured by the new trait‐specified PD (e.g., with traits such as Intimacy Avoidance, Suspiciousness, or Withdrawal; Skodol et al, 2011).…”
Section: Examples Where Pds and Psychotic Symptoms Meetmentioning
confidence: 99%
“…Nevertheless, the transdiagnostic concept of paranoia (the attribution of malevolent/hostile intents to others) might still bear relevance for the broader spectrum of PDs. Indeed, it can be a feature of virtually all categorical PDs (e.g., borderline, histrionic, obsessive‐compulsive) and many “syndromic” disorders (e.g., depression, posttraumatic stress disorder; Fanti et al, 2023). The paranoia continuum, while calling for more research, might be a mechanism linking personality to psychosis by spanning a wide range of nonpsychotic and psychotic experiences (ranging from, e.g., fear of rejection to ideas of reference and persecution; Fanti et al, 2023).…”
Section: Examples Where Pds and Psychotic Symptoms Meetmentioning
confidence: 99%
“…Results of a systematic review of Fanti et al (2023) revealed that paranoia may be transdiagnostic in a variety of personality disorder diagnoses. They found evidence of mild-to-severe paranoia not only in paranoid personality disorder and schizotypal personality disorder but also in borderline personality disorder as well.…”
mentioning
confidence: 99%